Sosialisasi Peningkatan Ketahanan Bangunan Sekolah Di Kabupaten Tapanuli Selatan : Solusi Dari Kajian Non-Linier Perilaku Soft Storey - Harahap, Sahrul; Hasibuan, Erwina Azizah; Afniria, Afniria; Nasution, Alvi Sahrin (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
This service aims to mitigate soft storeys on the resilience of school buildings in South Tapanuli Regency. This socialization activity was held at the South Tapanuli Regency Education Office. The targets of this activity were the Principal and representatives of the Education Office and BPBD with a total of 30 participants. The steps for implementing this service began with presenting material about the Earthquake in South Tapanuli and Soft Storeys. Continued with a Workshop/Practice discussing Soft Storey Identification using the layout of each school building. At the end of the activity, finding solutions/discussions related to the policy of Integrating soft storey mitigation in school budget planning